THE INFLUNTIAL IMPACTS OF METACOGNITIVE READING STRATEGIES IN MODERN EFL READING CONTEXTS - kristian florensio wijaya (Unit Pengembangan Bahasa UIN Sayyid Ali Rahmatullah Tulungagung, 2022)
The presented modern EFL reading learning complexities cannot be constantly overlooked by second language reading instructors since language learners oftentimes experience dispiriting, energy-draining, and frustrating reading experiences. Aligned with these above-mentioned L2 reading learning issues, it is indispensably important for EFL educators to start incorporating metacognitive reading strategies during the ever-changing literacy programs. Previous researchers strongly noted that the precise utilization of metacognitive reading strategies can provide a sound foundation for EFL learners to gain deeper insights into their chosen reading texts and exert better controls on the ongoing reading learning dynamics. This current-small scale library study was enacted as an attempt to exhaustively investigate the specific influential impacts promoted by metacognitive reading strategies in modern EFL reading contexts. To meet this study’s major demand, the researcher critically selected thirty pieces of literature that corresponded with this research area. As observed in the obtained research results, metacognitive reading strategies can pave a new enlightening pathway for globalized EFL learners to transfigure into more competent L2 readers and attain more satisfying reading learning outcomes. Finally, worldwide EFL educationalists should activate metacognitive reading strategies at the onset of their literacy programs to enable learners to become self-initiators possessing a higher level of intellectual curiosity and orchestrate a vast range of efficient reading strategies to meet the targeted reading learning demands.